Assessment of the per- and polyfluoroalkyl substances analysis under the Stockholm Convention – 2018/2019. (February 2023) - van der Veen, Ike; Fiedler, Heidelore; de Boer, Jacob
Abstract: The comparability of laboratories for the analysis of per- and polyfluoroalkyl substances (PFAS) was assessed in the fourth round (2018/2019) of a series of interlaboratory assessments coordinated by the United Nations Environment Programme (UNEP) in support of the Stockholm Convention quality assurance activities as to persistent organic pollutants (POPs) laboratories reporting data under this Convention. The participating laboratories were asked to analyse PFAS concentrations in a test solution of the target compounds, in the four core matrices of the global monitoring plan (GMP), human milk, human plasma, an air extract, and water, and in a sediment and a fish matrix. 39 participating laboratories submitted PFAS data for one or more test materials. The majority of the participating laboratories originated from the Asia-Pacific region, and from the 'Western European and other groups' (WEOG). Only one laboratory from the group 'Latin America and Caribbean' (GRULAC), and two from the Central and Eastern Europe (CEE) region submitted results. None of the African laboratories submitted data. The coefficients of variation (CVs) varied from 7% to 24% (mean 14%) for the test solution. Mean CVs for all matrices, except for the human plasma test material (18%), were above the satisfactory limit of 25%. The highest mean CV was found for human milk (61%). In total 1457 z-scores were assigned of which 64% were satisfactory (|z| < 2). Instrumentation used was mainly high-performance liquid chromatography (HPLC), in combination with various mass spectrometric (MS) techniques, in most cases tandem MS (MS/MS). Additional PFAS beyond perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA), which are listed at the Stockholm Convention POPs list, as well as water as a matrix for PFAS only and human plasma were added as a service for the laboratories. Graphical abstract: Image 1 Highlights: Worldwide Interlaboratory assessment on per- and polyfluorinated alkyl substances. Increasing number of participants compared to previous rounds. Performance of individual participants vary. Mean coefficients of variation were above 25% except for the human plasma material. Lack of participation from Africa, and low participation degree in GRULAC region.